2014
DOI: 10.5194/nhess-14-891-2014
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment study of fire following an earthquake: a case study of petrochemical enterprises in China

Abstract: Abstract.After an earthquake, the fire risk of petrochemical enterprises is higher than that of other enterprises as it involves production processes with inflammable and explosive characteristics. Using Chinese petrochemical enterprises as the research object, this paper uses a literature review and case summaries to study, amongst others, the classification of petrochemical enterprises, the proportion of daily fires, and fire loss ratio. This paper builds a fire following an earthquake risk assessment model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We conducted robustness checks in two ways. First, we added additional control variables regarding natural disasters, as previous studies have shown that the incidence or potential threat of natural disasters in an area could lower migrants’ willingness to live there [ 35 , 50 , 51 ]. Therefore, in our basic OLS model, we added a dummy variable indicating whether there have been tremendous hazards in the past ten years at the destinations.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted robustness checks in two ways. First, we added additional control variables regarding natural disasters, as previous studies have shown that the incidence or potential threat of natural disasters in an area could lower migrants’ willingness to live there [ 35 , 50 , 51 ]. Therefore, in our basic OLS model, we added a dummy variable indicating whether there have been tremendous hazards in the past ten years at the destinations.…”
Section: Resultsmentioning
confidence: 99%